The gynecological controls in the elderly female dogs - Erdoğan, Güneş (Journal of the Hellenic Veterinary Medical Society, 2022)
In canine geriatric medicine has many different research areas such as cardiology, endocrinology, dentistry. However, diagnosing many related diseases and complications can be late related to thoughts that spayed dog's genital exams are thought of as unneeded approaches. Reproductive infections, mammary/gynecologic tumoural diseases, and their complications decrease their life quality and have a considerable mortality rate in aged intact and spayed bitches. Therefore, an effective gynecologic health check program supported with different imaging techniques is highly needed in small animal clinics. In this review, it is planned an annual gynecologic examination for older/geriatrics dogs and presented the main steps to early diagnose and prevent genital diseases with high mortality and lower their life quality and longevity.